Dampak Pemberian Pupuk Kompos Salak Terhadap Pertumbuhan Dan Hasil Bayam Hijau (Amaranthus viridis L.) Di Desa Gununggiana, Madukara, Banjarnegara, Jawa Tengah - Ana Maghfiroh Hayati; Rennanti Lunnadiyah Aprilia (Jurnal Penelitian Pertanian Terapan, 2025)
Green amaranth (Amaranthus viridis L.) is a nutrient-dense leafy vegetable widely consumed for its protein, vitamins (A, B, C), and mineral salts (Ca, P, Fe). This study evaluated the effect of salak-waste compost on the growth and yield of green amaranth. A completely randomized design (CRD) with six single-factor compost rates and four replications was used: D1 = 0 g, D2 = 250 g, D3 = 500 g, D4 = 750 g, D5 = 1,000 g, and D6 = 1,250 g of compost per polybag. The experiment was conducted from March to August in Gununggiana Village, Banjarnegara, Indonesia. Observations included plant height, leaf number, leaf area, root length, whole-plant fresh and dry weights, and root fresh and dry weights; air temperature and relative humidity were recorded as environmental covariates. Data were analyzed using one-way ANOVA at α = 0.05, and significant means were separated with Duncan’s Multiple Range Test (DMRT, 5%). Treatments 1,250 g soil + 750 g compost (D4) and 1,000 g soil + 1,000 g compost (D5) produced the highest mean values for most growth and yield variables (p < 0.05), indicating that these combinations can be recommended to enhance the performance of green amaranth under the conditions of this study.